3h+4T+2U=

Simple and best practice solution for 3h+4T+2U= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3h+4T+2U= equation:


Simplifying
3h + 4T + 2U = 0

Reorder the terms:
4T + 2U + 3h = 0

Solving
4T + 2U + 3h = 0

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Add '-2U' to each side of the equation.
4T + 2U + -2U + 3h = 0 + -2U

Combine like terms: 2U + -2U = 0
4T + 0 + 3h = 0 + -2U
4T + 3h = 0 + -2U
Remove the zero:
4T + 3h = -2U

Add '-3h' to each side of the equation.
4T + 3h + -3h = -2U + -3h

Combine like terms: 3h + -3h = 0
4T + 0 = -2U + -3h
4T = -2U + -3h

Divide each side by '4'.
T = -0.5U + -0.75h

Simplifying
T = -0.5U + -0.75h

See similar equations:

| .5w-1.32+1.2w=0.4w+8.04 | | 12/-25 | | ln(2x-1)=3.8 | | x+5+x-1+x+4+x=360 | | 3(y+1)=8 | | 3b+7a=54 | | 3b+1=7 | | 5a+3b-7a+4b=0 | | a/b=c/d(x-m) | | X=-2/-3 | | 7900*57.3= | | 3x+4=127 | | 3x-4+127=180 | | 3x-4=127 | | 25v^2+70vf+49f^2= | | -7(10-2x)=-196 | | 9m^2-24m+16= | | 2-3n=8+n | | X+8+x+28+2x=180 | | 1/x2 | | 3(2-n)=8+n | | 13.8*148/360= | | 15843754684689148958943165897365734965794627803679346893467894567689476892796802768287267859276895276982762898956789257628976892576895769857687675894679503838696374568568942658975946578175798217q+653785975878.57q=1 | | 3(10+7x)=72 | | 65+5n=11n-7 | | 1233478768697897678956807x=67382965829657829654789365 | | 1233478768697897678956807=67382965829657829654789365 | | 4(49b^2-25)= | | 6f*6f= | | 6-7x=7x-148 | | -2p+15=-5p-4 | | 196b^2-100= |

Equations solver categories